The significance of non-controlled natural light, temperature and humidity in the commercial micropropagation of Solanum tuberosum L. Cultivar Diamant (Plant Tissue Culture and Biotechnology, 2015)
The aim of our study was to reduce the unit cost of in vitro micropropagation of the Solanum tuberosum cultivar Diamant widely cultivated in Bangladesh with the guarantee that the quality and quantity of the in vitro plants produced was not jeopardized. This was done by entirely replacing the conventional micropropagation conditions of maintaining the in vitro plants in a controlled room whose temperature varies between 25 and 30°C, its humidity between 60 to 70% and its light intensity of 20,238 to 20,409 for 19 hours; with a room whose roof was made of corrugated plastic sheets that allow a partial passage of natural light. Under this conditions the amount of light, temperature and humidity were not controlled. During the time work the temperatures in this non-conventional room fluctuate between 14 and 40°C, the light intensities were between 20,017 to 20,687 Lux and the humidity between 40 to 90%. Experiments were initiated in May, 2009 through March, 2014 covering summer, rainy and winter seasons. After two years of laboratory research and two years of field studies, we have not found differences between yield production of the micropropagated plants grown under control and non-controlled conditions, very often the latter plants were robust and adapted faster when transfer to field conditions. All plants used in the field experiments were no more than seven in vitro passages. A RBCD yield trail of the plants was done during two seasons and it was no found any difference in yield between them. Moreover, a yield trail of the minitubers to produce breeder seed (second generation) was done during the season 2013-2014 and no differences were found between the controls and the tubers derived from the low cost.Plant Tissue Cult. & Biotech. 24(2): 131-139, 2014 (December)